CEO characteristics and financial restatement: The case of CEO turnover in Malaysia - Ishak, Rokiah; Md Yusof, Mohd 'Atef; Amran, Noor Afza; Aripin, Norhani (Universiti Utara Malaysia, 2014)
This study examines the incidence of financial restatement in CEO turnover firms. Using 78 CEO turnover firms from 2008 to 2010 among nonfinancial institution, we find that the age of the CEO and forced turnover influence restatement in the year prior to CEO turnover. Specifically, older CEOs have higher probability of restating financial statement as they may wish to hold to the l ast bonus/pay they would likely receive.We also document some evidence of management entrenchment hypothesis that CEO ownership may lower financial restatement.Firm characteristics such as size, Big 4 and growth as measure by market to book value have a positive relationship with restatement which suggests that big companies with high growth have higher probability of restatement.The study also supports the argument of debt as a monitoring cost as debt is argued to constraint opportunistic earnings management behavior including restatement.